Setor informal: uma categoria imprecisa - Santos, Márcia dos (2009)
Due to the hegemony of capitalism system that globalization has set, regional and global markets have suffered many deep changes and some categories and businesses have vanished while others have been created. Among the new ones, the informal sector has arisen strongly and this study is exactly about this issue based on the following title: informal sector an unclear category . This study aims to codify the different concepts of informality and its subsystems in order to have a better understanding of this relevant and meaningful economic sector for Brazilian market, consistently aiming to subsidize initiatives in the subsystems supported by the public sector. Methodologically, this study brings for discussion the dynamics and standards of Brazilian labor market since the 90 s by thoroughly and critically describing the customs opening and its consequences to national productive sectors, denationalization, informal sector, informal activities, regionalisms, informal work characteristics and its categories. It discusses the concept of informality, residual concept and informality consequences, cost and the informal concept segmentation